Synthesis, anticancer and apoptosis-inducing activities of quinazoline-isatin conjugates: epidermal growth factor receptor-tyrosine kinase assay and molecular docking studies - Adel S. El-Azab; Abdullah Al-Dhfyan; Alaa A.-M; Laila A. Abou-Zeid; Hamad M. Alkahtani; Abdulrahman M. Al-Obaid; Manal A. Al-Gendy (Taylor & Francis Group, 2017)
A new series of quinazolinone compounds 16-34 incorporating isatin moieties was synthesized. The antitumor efficacy of the compounds against MDA-MB-231, a breast cancer cell line, and LOVO, a colon cancer cell line, was assessed. Compounds 20, 21, 22, 23, 25, 27, 28, 29, 30, 31, 32, 33, and 34 displayed potent antitumor activity against MDA-MB-231 and LOVO cells (IC50: 10.38-38.67 μM and 9.91-15.77 μM, respectively); the comparative IC50 values for 5-fluorouracil and erlotinib in these cells lines were 70.28 μM, 22.24 μM and 15.23 μM, 25.31 μM respectively. The EGFR-TK assay and induction of apoptosis for compound 31 were investigated to assess its potential cytotoxic activity as a representative example of the novel synthesized compounds. At a concentration of 10 μM, compound 31 exhibited efficient inhibitory effect against EGFR-TK and induced apoptosis in MDA-MB-231 cells. Furthermore, a molecular docking study for compound 31 and erlotinib was performed to verify the binding mode toward the EGFR kinase enzyme, and showed a similar interaction as that with erlotinib alone. Graphical Abstract: Compound 31 showed potent antitumor activity and efficient inhibitory effect against EGFR-TK and induced apoptosis of MDA-MB-231 cells at a concentration of 10 μM.